Reproductive Biology And Phenological Observation of Three Calamus Species in Peninsular Malaysia - Abdullah, Mohd Zaki (2000)
Knowledge on reproductive biology is important for genetic improvements program. This study aimed at determining the reproductive biology and phenological behavior of Calamus palustris Griff. var. malaccensis Becc., Calamus scipionum Loureiro, and Calamus ornatus Blume., from natural populations. Seven sites throughout Peninsular Malaysia i.e. Hutan Simpan Mata Ayer, Bukit Larik, Setia Enggor, Linggi, Batu Kurau, Bukit Besi and Ulu Serting were chosen for the studies. In the basic study, observations on the reproductive biology including floral morphology, phenology and regeneration behaviour were made. For the study on floral morphology, only C. scipionum and C. palustris were selected. The flower structures of C. scipionum and C. palustris were similar. The differences noted were in the colour and sizes of the flowers. The male flowers of C. scipionum were dark brown and yellowish in C. paiustris. The female flowers of C. paiustris were pale yellow in colour and dark brown in C. scipionum. In terms of flower size, both male and female flowers of C. scipionum were bigger than those of C. paiustris and for each species female flowers were bigger than male flowers. C. scipionum had longer inflorescences and main rachis compared to C. paiustris. However, there were no differences in terms of the number of main rachis and rachilla per inflorescence and rachilla length. In the female inflorescence, C. scipionum had longer inflorescence, longer main rachis and also contained more rachilla compared to C. paiustris. Differences in the timing of flowering and fruiting were observed among the different climatic zones in all the three species. Fruit production took 8-9 months for C. paiustris and 12-13 months for C. scipionum and C. ornatus. However, the variation on number of C. paiustris wildings occurring under the rubber plantation and forested areas showed no significant difference. The information gained for this study can be used for breeding and genetic improvement programme for these species.